Analysis theorem of unique common fixed point for four maps based on partial –b– metric spaces - Ban Hasan; Hayder Abdulameer Abbas (Institute of Advanced Engineering and Science, 2019)
In this paper, An important definitions are to be used to prove the existence of a common fixed point theorem for four mappings incomplete, partial – b – metric spaces, as well as prove a unique common fixed point by assuming another point and getting that, these points are finally equal. We presented an example thus enhancing us the outcome.